Molecular characterization of XopAG effector AvrGf2 from Xanthomonas fuscans ssp. aurantifolii in grapefruit. (10th June 2016) - Gochez, Alberto M.; Shantharaj, Deepak; Potnis, Neha; Zhou, Xiaofeng; Minsavage, Gerald V.; White, Frank F.; Wang, Nian; Hurlbert, Jason C.; Jones, Jeffrey B.
Summary: Xanthomonas fuscans ssp. aurantifolii group C strains exhibit host specificity on different citrus species. The strains possess a type III effector, AvrGf2, belonging to the XopAG effector gene family, which restricts host range on citrus. We dissected the modular nature and mode of action of AvrGf2 in grapefruit resistance. XopAG effectors possess characteristic features, such as a chloroplast localization signal, a cyclophilin‐binding domain characteristic amino acid sequence motif (GPLL) and a C‐terminal domain‐containing CLNAxYD. Mutation of GPLL to AASL in AvrGf2 abolished the elicitation of the hypersensitive response (HR), whereas mutation of only the first amino acid to SPLL delayed the HR in grapefruit. Yeast two‐hybrid experiments showed strong interaction of AvrGf2 with grapefruit cyclophilin (GfCyp), whereas AvrGf2‐SPLL and AvrGf2‐AASL mutants showed weak and no interaction, respectively. Molecular modelling and in silico docking studies for the cyclophilin–AvrGf2 interaction predicted the binding of citrus cyclophilins (CsCyp, GfCyp) to hexameric peptides spanning the cyclophilin‐binding domain of AvrGf2 and AvrGf2 mutants (VAGPLL, VASPLL and VAAASL) with affinities equivalent to or better than a positive control peptide (YSPSA) previously demonstrated to bind CsCyp. In addition, the C‐terminal domain of XopAG family effectors contains a highly conserved motif, CLNAxYD, which was identified to be crucial for the induction of HR based on site‐directed mutagenesis (CLNAxYD to CASAxYD). Our results suggest a model in which grapefruit cyclophilin promotes a conformational change in AvrGf2, thereby triggering the resistance response.